Return to Sport after ACL Surgery: A Comparison between Two Different Reconstructive Techniques - Baldassarri, Matteo; Perazzo, Luca; Ghinelli, Diego; Ricciarelli, Marco; Pilla, Federico; Buda, Roberto (The Journal of Knee Surgery, 2019)
The anterior cruciate ligament reconstruction (ACLR) has become a very common surgical procedure. One of the main success indicators of the surgical procedure is the return to preinjury sporting level. In recent years, reconstructive techniques have been geared toward less morbidity and optimized ligaments process to speed up the recovery of sports activity. This study compares clinical and imaging data, to evaluate the timing of return to sport, of two populations undergoing ACLR using two different techniques: ACLR with hamstring maintaining tibial insertion (MHG) and an all-inside technique with complete hamstring detachment (DHG). Patients were clinically evaluated with Marx rating scale, International Knee Documentation Committee (IKDC) score, and Tegner activity scale at a minimum follow-up (FU) of 4 years. The two groups have homogeneous characteristics: age, sex, type, and level of sports activity. Since November 2012, 59 patients with unilateral ACL insufficiency underwent ACLR: 31 patients using the MHG technique and 28 patients using the DHG technique. In both groups, a significant improvement in the clinical scores of the administered tests was observed. The MHG group reported a higher percentage of normal knees (83.8%) compared with the DHG group (78.6%). IKDC subjective score improved at each FU. Comparing the two techniques, at 12 months' FU the MHG group achieved better IKDC results (89.6) compared with the DHG technique (84.2). Marx and Tegner score values improved over time reaching comparable results at final FU. At final FU, 98% of patients returned to the same preinjury professional sporting level. Both techniques have been able to provide good clinical results. The MHG group, however, had a resumption of sports activity of the same level and intensity slightly longer (6.3 months) than that in the DHG group (5.9 months). Furthermore, the resumption of training and athletic gestures for the type of sport practiced was earlier than the DHG group. However, in the long run the level of sporting activity leveled in both groups, demonstrating the effectiveness of both techniques.
Keywords: anterior cruciate ligament; knee; sport return